Assessment of shock in emergency: Narrative review - Silwal, Shruti; Devkota, Prerit; Sinha, Puja; Raut, Randip; Shrestha, Ashis (Journal of General Practice and Emergency Medicine of Nepal, 2021)
Shock is an important clinical condition presenting to the emergency department. Pathophysiology of septic, cardiogenic, hemorrhagic, obstructive, and anaphylactic shock are different however clinical assessment tools are the same and limited. It is important to identify shock in its early phase or the patient at risk of shock in the emergency department. There is no accurate clinical tool to identify the early stage of shock. Moreover, it is also important to assess fluid responsiveness to shock, available clinical and biochemical parameters respond differently to fluid resuscitation and none of the tools had 100% sensitivity and specificity. Therefore, this article reviews the available clinical and biochemical parameters to assess and monitoring fluid responsiveness in shock.